Morphophonemic Allomorphs Of The Prefix Sa- In Toba Batak Verbs: A Generative And Pedagogical Perspective - Esron Ambarita; Charles David Marudut Silalahi; Elita Modesta Br. Sembiring; Veraci Silalahi (Journal of Classroom Action Research, 2026)
The research fills an essential void in morphological studies by examining the overlooked morphophonemic allomorphs of the prefix sa- [sa-] in Toba Batak, an at-risk Austronesian language. This research addresses this gap by utilizing a customized version of Halle’s (1973) generative morphology framework, specifically adapted to the distinct linguistic characteristics of Toba Batak, to examine data gathered from 12 native speakers in Samosir Regency and Toba Samosir Regency. As the technical novelty, the research uncovers four unique morphophonemic allomorphs  of the prefix sa- [sa-] in Toba Batak based on a generative and pedagogical perspective, namely, (i) sam- [sam-], (ii) san- [san-], (iii) sang- [saŋ], and (iv) sangng- [saŋŋ-]. The study highlights that the prefix sa- [sa-] in Toba Batak is productive, generating a wealth of grammatical and lexical meanings that stem exclusively from alternating forms. The modified Hallean model, which includes orthographic and phonological rules, effectively captures these subtleties, providing a novel framework. The consequences reach applied areas such as pedagogical perspective, revitalization, language instruction, and cultural renewal, highlighting the necessity of protecting regional languages like Toba Batak in the face of globalization. The implications extend to connect theoretical linguistics with practical conservation activities, promoting additional research on lesser-known languages Keywords: Morphophonemic Allomorphs, Prefix sa-, Toba Batak Verbs, Generative and Pedagogical Perspective